TINJAUAN HUKUM PENJATUHAN SANKSI ADAT TERHADAP PEMBURUAN DAGING PENYU SEBAGAI SATWA YANG DILINDUNGI (STUDI KASUS KECAMATAN PULAU BANYAK) - Khatijah, Siti; Trisna, Nila (UNES Law Review, 2023)
Article 21 paragraph 2 of law number 5 of 1990 concerning living natural resources and their ecosystems. Violation of the provisions of article 21 paragraph 2 is regulated in article 40 of law number 5 of 1990. However, the reality that occurred in the Pulau Banyak sub-district was resolved through customary law that grew within the community and the community still violates the provisions of customary law that exist in society. The type of research method is empirical juridical using primary data through interview data, literature study of written materials such as books and documents. The results of this study say that in the Pulau Banyak District area there are still violations of customary law provisions that live in the community, so that people still violate customary law regarding turtle protection. Based on the case of turtle meat hunting, customary law cannot provide a definite resolution, so it is contrary to the law, therefore it must be resolved through positive law.